IDENTIFIKASI PROSPEK HIDROKARBON MENGGUNAKAN METODE INVERSI SIMULTAN PADA LAPANGAN TEAPOT DOME, WYOMING - Ida Herawati; Muhammad Ilham Al Haj (Program Studi Teknik Geofisika FITK UHO, 2023)
First Wall Creek and Second Wall Creek is reservoir interval at Teapot Dome Field, Wyoming, USA To determine lithology and fluid type distribution in this formation, this study conducts seismic attributes mapping using inversion process. Simultaneous inversion is applied to angle gather data to obtain seismic attribute values for First Wall Creek (F1WC) and Second Wall Creek (F2WC) reservoirs. Cross-plot analysis shows that P-Impedance, Vp/Vs ratio, lambda-rho and mu-rho attributes can distinguish reservoir zone from non-reservoir zone. Simultaneous inversion results are P-Impedance, S-Impedance, and density volume, therefore LMR (Lambda-Mu-Rho) attributes calculation is needed. From cross-plot analysis and inversion results, lithology and fluid distribution are interpreted. For F1WC reservoir zone, lambda-rho <32.2 Gpa*g/cc indicate sandstone areas with Vp/Vs Ratio <1.77 indicate brine inclusions. For F2WC zone, lambda-rho <33 Gpa*g/cc indicate sandstone area and oil-inclusion area is indicated by P-Impedance <30000 ft/s*g/cc and Vp/Vs Ratio <1.8. From attributes maps, oil reservoir in F2WC zone is possible accumulated at northwest part of study area.